Kualitas Pelayanan Publik Bidang Administrasi Dalam Perspektif Good Governance - Rio Andika Setiawan; Wydha Mustika Maharani; Muhammad Nasyirudin (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The research conducted has the aim of knowing and seeking an overview of the quality of public services in the field of administration regarding the perspective of good governance in public services at the Rembang Village Office, Blitar City. Research conducted using qualitative methods with a case study research approach (case study). Data collection techniques were carried out using participatory observation methods, conducting interviews with selected informants and conducting literature studies and examining data sources from documents related to research. From all the data that has been collected, the researcher processes it using data collection, data condensation, data presentation (information display), and verification of research or conclusions, then the researcher checks the validity of the data using 1) Credibility test which consists of technical triangulation techniques, data source triangulation, time triangulation, 2) transferability tests in which researchers compile research reports by providing detailed, systematic, and reliable descriptions, 3) reliability tests are carried out through a series of audit processes by supervisors and, 4 ) Objectivity Test (Confirmability) in which the results of this study were tested through a series of examination processes carried out by the supervisor and the team of examiners through the final exam. Based on the results of the study, 1) the quality of public services in the administrative field at the Rembang Kelurahan Office is already good with evidence of the facilities, facilities and infrastructure provided by the Rembang Kelurahan Office being sufficient and supporting public services in public services at the office. In addition, professionalism, timeliness and speed in providing appropriate services are important factors regarding improving the quality of public services; 2) Administrative public services at the Rembang Village Office apply the principles of good governance, namely participation, rule of law, and transparency in public services by involving the community in all service activities, starting from the policy formulation stage to the evaluation level. This can improve the quality of public services and strengthen public trust in the government; 3) Supporting factors in public services in the field of administration at the Rembang Village Office, namely: a) adequate facilities and infrastructure; b) there is professionalism in providing services, as well as being responsive to customers, c) services that are in accordance with operational standards and are not complicated. While the inhibiting factors for public services at the Rembang Village Office are a) the lack of completeness of the requirements brought by the community; b) the public's lack of understanding of the requirements when applying for documents; c) the dissemination of information related to public services is still limited in order to improve public services through quality.